'International Shanghai' (1863–1931): Imperialism and private authority in the Global City. (7th December 2021) - Cong, Wanshu; Mégret, Frédéric
Abstract: At the intersection of imperial rule and private power, Shanghai rose to international prominence in the second half of the nineteenth and first half of the twentieth century. It did so by taking advantage of the extraterritorial status and the dynamic, cosmopolitan population of the International Settlement. In evaluating the fate of the Shanghai Municipal Council, we seek to ascertain how private authority could have been constituted on a transnational basis within the framework of a treaty port. The rise of Shanghai was linked to some of the ambiguities of overlapping imperial rule and the possibilities it created for legal and governance experimentation. This is particularly clear in realms most associated with sovereign power, namely the International Settlement's attempts to claim some taxation power and maintain law and order. That power, however, was interstitial at best and the product of fragile balances, as shown by the Council's ultimate failure to secure a full international legal status for Shanghai. Nonetheless, the rise and fall of the International Settlement at Shanghai are worth reflecting upon, not only in relation to the history of China, imperialism and international law, but also as a way of thinking how the authority of large metropolitan centres might be constituted.